Economy and finance in Panama: An imperative evocation to human rights - Bohoslavsky, Juan Pablo (2018)
This article analyses the economy and finances of Panama from a human rights perspective. It first presents the adverse implications of illicit financial flows on human rights. It then describes the Panamanian legal and institutional framework, in particular the country´s international obligations and commitments, as well as the banking and financial sector of the country. It also presents the “Panama Papers,” including the scandal outbreak, policies adopted by the government as well as those additional measures still needed. Issues related to the country’s economic growth, inequality and human rights are also discussed, and the implications of infrastructure projects for persons and groups in Panama, including indigenous peoples, are critically studied. After the conclusions the recommendations that the author made to the Panamanian government as Independent Expert of the UN after his visit to the country are presented.